اﻷﻟﻔﺎظ واﻟﻤﺼﻄﻠﺤﺎت اﻷﺳﺎﺳﯿﺔ ﻟﻠﻘﺎﻧﻮن اﻟﺪوﻟﻲ اﻟﺨﺎص ّﻓﻲ إﺳﺘﻌﻤﺎل اﻟﻘﺮآن اﻟﻜﺮﯾﻢ ـ دراﺳﺔ دﻻﻟﯿﺔ ﺗﺄﺻﯿﻠﯿﺔ - د.ﻗﺴﻤﺔ ﻣﺪﺣﺖ ﺣﺴﯿﻦ دروﯾﺶ اﻟﻘﯿﺴﻲ د.رﺷﯿﺪ ﻣﺠﯿﺪ ﻣﺤﻤﺪ اﻟﺮﺑﯿﻌﻲ (مجلة كلية التربية للبنات, 2019)
The research consists of a preface followed by an Introduction which includes the private International Law, its sources, in addition to four sections and a conclusion.Finally, the research concludes with a list of the sources used and also a list of terms and words in English or Latin Language. The four sections of the researchare: Sectionone: Nationality terms group . Sectiontwo: group of terms of Domicil(home country) and status of foreigners (Aliens) Sectionthree: group of terms of the conflict ofLaws, conflict of the International JudicialJurisdiction,and, Enforcing ForeignJudgments. Sectionfour: The semantic phenomena which came in the basic terms and words of the private International Law.